Earthquake Swarm in Santorini, Greece: Recurrence Quantification Analysis and Investigation of Potential Causal Relationship with Tidal Forces - S. Maltezos; A. Georgakopoulou (Mathematical Geosciences, 2026)
In early 2025, an unusual earthquake swarm began in the surrounding area of the small uninhabited islet Anydros, located between the Santorini and Amorgos islands in Greece. The nature of this seismic activity motivated the study of its dynamical and statistical features and the investigation of a potential causal relationship between the normal component of tidal forces caused by the moon and the sun. To investigate these questions, three complementary approaches were employed: recurrence quantification analysis and its associated metrics, used to identify recurrent states in complex dynamical systems, linear and nonlinear Granger causality tests, and convergent cross mapping to detect nonlinear causal interactions. In the same context, a global statistical analysis of earthquakes in the highest magnitude range was performed to examine the probability of occurrence around the four lunar phases. Based on this analysis, an overall probability density function model was constructed.